The effect of the stress autism mate app on perceived stress, coping, and resilience in adults with autism: a single-case experimental design - Hoeberichts, Kirsten; Roke, Yvette; Niks, Irene; van Harten, Peter N. (Frontiers in Psychiatry, 2024)
Introduction The mobile health application “Stress Autism Mate” (SAM) was designed to support adults with autism in identifying and managing daily stress. SAM measures stress four times daily, provides a daily and weekly stress overview, and provides personalised stress reduction advice. This study aimed to assess the effectiveness of SAM over four weeks in reducing perceived stress and internalised stigma, and enhancing coping self-efficacy, quality of life, and resilience among adults with autism. Methods Using an A1-B-A2 single-case experimental design, the effect of using SAM on adults with autism was assessed. The phases consisted of A1; treatment as usual (TAU), B; introducing SAM, and finally A2; follow-up with TAU and without the use of SAM. Each phase lasted four weeks, and data were collected via questionnaires before and after each phase. Linear mixed models were used for data analysis. Results Results show significant reductions in perceived stress levels, increased coping self-efficacy, and improved perceived health and psychological well-being after using SAM. Furthermore, increased resilience, and decreased internalised stigma were reported after follow-up. Discussion In conclusion, this study highlights SAM as a valuable tool for empowering adults with autism to reduce stress and internalised stigmaand to improve coping self-efficacy, psychological well-being, and resilience.